Sarmentine, a natural herbicide from Piper species with multiple herbicide mechanisms of action - Dayan, Franck E.; Owens, Daniel K.; Watson, Susan B.; Asolkar, Ratnakar N.; Boddy, Louis G. (Frontiers in Plant Science, 2015)
Sarmentine, 1-(1-pyrrolidinyl)-(2E,4E)-2,4-decadien-1-one, is a natural amide isolated from the fruits of Piper species. The compound has a number of interesting biological properties, including its broad-spectrum activity on weeds as a contact herbicide. Initial studies highlighted a similarity in response between plants treated with sarmentine and herbicidal soaps such as pelargonic acid (nonanoic acid). However, little was known about the mechanism of action leading to the rapid desiccation of foliage treated by sarmentine. In cucumber cotyledon disc-assays, sarmentine induced rapid light-independent loss of membrane integrity at 100 µM or higher concentration, whereas 3 mM pelargonic acid was required for a similar effect. Sarmentine was between 10 and 30 times more active than pelargonic acid on wild mustard, velvetleaf, redroot pigweed and crabgrass. Additionally, the potency of 30 µM sarmentine was greatly stimulated by light, suggesting that this natural product may also interfere with photosynthetic processes. This was confirmed by observing a complete inhibition of photosynthetic electron transport at that concentration. Sarmentine also acted as an inhibitor of photosystem II on isolated thylakoid membranes by competing for the binding site of plastoquinone. This can be attributed in part to structural similarities between herbicides like sarmentine and diuron. While this mechanism of action accounts for the light stimulation of the activity of sarmentine, it does not account for its ability to destabilize membranes in darkness. In this respect, sarmentine has some structural similarity to crotonoyl-CoA, the substrate of enoyl-ACP reductase, a key enzyme in the early steps of fatty acid synthesis. Inhibitors of this enzyme, such as triclosan, cause rapid loss of membrane integrity in the dark. Sarmentine inhibited the activity of enoyl-ACP reductase, with an I50app of 18.3 µM. Therefore, the herbicidal activity of sarmentine appears to be a complex process